2012
DOI: 10.1016/s1836-9553(12)70106-6
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training improves sleep quality in middle-aged and older adults with sleep problems: a systematic review

Abstract: Participation in an exercise training program has moderately positive effects on sleep quality in middle-aged and older adults. Physical exercise could be an alternative or complementary approach to existing therapies for sleep problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
390
5
28

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 475 publications
(443 citation statements)
references
References 42 publications
20
390
5
28
Order By: Relevance
“…Nonetheless, some studies show that exercise training programs improve sleep health in other populations with different diseases and in middle-aged and older adults. [36][37][38] Passos et al 36 suggested that aerobic exercise may reduce presleep anxiety and improve sleep quality in patients with primary insomnia. King et al 37 evaluated the effect of 4 months of exercise on sedentary individuals with reported sleep complaints and demonstrated that exercise programs improved their self-rated sleep quality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, some studies show that exercise training programs improve sleep health in other populations with different diseases and in middle-aged and older adults. [36][37][38] Passos et al 36 suggested that aerobic exercise may reduce presleep anxiety and improve sleep quality in patients with primary insomnia. King et al 37 evaluated the effect of 4 months of exercise on sedentary individuals with reported sleep complaints and demonstrated that exercise programs improved their self-rated sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…40 Exercise is commonly believed to improve sleep quality. 38 However, the exact mechanisms of how exercise training improves sleep quality in patients with COPD are unclear. Consideration of the mechanisms underlying the effect of exercise on sleep quality is beyond the scope of this study, but they are believed to consist of a complex set of activities, including physiological and psychological benefits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also concluded a minimum of two sessions per week of at least 45 minutes duration each to induce effects. One possibly contributing factor to increased mental health could be the improved sleep quality that has been found in middle-aged and older adults with sleep problems during exercise [71]. Depression is a major global cause of impaired health and is usually treated by means of antidepressants and/or psychotherapy.…”
Section: Physical Activity and Mental Healthmentioning
confidence: 99%
“…Moreover, a previous systematic review showed that aerobic exercise training improves overall sleep quality (ie. reduced latency to fall asleep, increased sleep time) 7 , suggesting that, despite the benefits of aerobic exercise, little attention has been given to other types of exercise (ie. strenght training).…”
Section: Introductionmentioning
confidence: 99%